(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate preliminary phytochemical constituents, determine total phenolic and flavonoid contents, and evaluate the antioxidant and antimicrobial activities of guava leaf ethanol extract. Subjects and methods: The extract was prepared using 70% ethanol-assisted ultrasonic extraction. Phytochemical constituents were screened qualitatively. Total phenolic and flavonoid contents were determined by Folin-Ciocalteu and AlCl₃ methods, respectively. Antioxidant activity was evaluated by DPPH, ABTS+ and NO assays; antimicrobial activity was assessed by agar well diffusion. Results: The extraction yield was 17.82%. The extract contained flavonoids, tannins, terpenoids, alkaloids, saponins, and other phytochemical groups. Total flavonoid and phenolic contents were 409.09 ± 8.46 mgQE/g and 295.34 ± 17.25 mgGA/g dry material, respectively. IC₅₀ values for DPPH, ABTS+ and NO assays were 31.87 ± 4.57, 37.42 ± 6.43, and 539.72 ± 5.87 µg/mL, respectively. The extract inhibited MRSA, MSSA, E.coli, P.vulgaris, and C.albicans, with the strongest activity against MRSA. Conclusions: Guava leaf ethanol extract is rich in polyphenols and flavonoids and exhibits notable antioxidant and antimicrobial activities.